KINERJA DINAS SOSIAL PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DALAM PENYALURAN BANTUAN ALAT BANTU BAGI PENYANDANG DISABILITAS - Lalas Sulastri; Dhea Fransiska Aprilyan; Muhammad Fauzi Nuriana; Rizka Siti Jumiati; Siska Nuraeni; Siti Nur'Aminah (FISIP Universitas Sebelas April, 2022)
This study aims to analyze the performance of the Office of Social Affairs for Women's Empowerment and Child Protection in Distributing Aid Aid for Persons with Disabilities. The method used in the preparation of this PPA is a qualitative method, with the variable being Performance. The sampling technique used is purposive sampling, namely the sampling technique of data sources with certain considerations. The informants were the Head of Division, Head of Social Services and Rehabilitation, Staff for Social Services and Rehabilitation, PPDI (Indonesian Association of Persons with Disabilities) and Assistants for Persons with Disabilities, with this a total of 4 informants. Meanwhile, the Miles and Huberman model used in data analysis with the following steps: Data Reduction, Data Presentation, Conclusion Drawing/Verification, and Triangulation. The results of this study indicate that the performance of the Social Service for Women's Empowerment and Child Protection has been going well although there are still obstacles. The obstacle in this research is the limited budget for the distribution of aids. Efforts made by the Office of Social Affairs for Women's Empowerment and Child Protection are re-submitting the budget. It is recommended to increase the amount of the APBD budget, and improve the quality of the manufacture of assistive devices, as well as improve vehicle facilities for the distribution of assistive devices for persons with disabilities.